Exploring Innovative Strategies for Sustainable Organizational Growth: A Case Study Analysis” - Teguh Setiawan Wibowo; Christina Wulansari; Endri Haryati; Agus Purbo Widodo (Cita konsultindo, 2024)
Sustainable organizational growth is a key factor for an organization to survive and continue to compete in dynamic market trend changes. To balance the complexity of a growing organization, it usually requires good management in the form of innovative strategies in management that support the organization to maintain its existence until now amidst many other organizations that have gone bankrupt. One of them that implements is PT. Pertamina (Persero). The aim is to explore and find what innovative strategies support sustainable organizational growth, namely PT. Pertamina (Persero). The method used is qualitative descriptive analysis supported by literature studies and internet searching. The result is that there are four main innovative strategies that support the sustainable growth of PT. Pertamina (Persero), namely product innovative strategies, process innovative strategies, business model innovative strategies, and disruptive innovative strategies. It is hoped that the application of these four innovative strategies will create products with better performance, minimize negative environmental impacts, reduce operational costs, create new sustainable sources of income, enable the development of new solutions, and create new competitive advantages that can adapt to changing market trends.